Dose Assessment of Cefquinome by Pharmacokinetic/Pharmacodynamic Modeling in Mouse Model of Staphylococcus aureus Mastitis - Yu, Yang; Zhou, Yu-Feng; Li, Xiao; Chen, Mei-Ren; Qiao, Gui-Lin; Sun, Jian; Liao, Xiao-Ping; Liu, Ya-Hong (Frontiers in Microbiology, 2016)
This work aimed to characterize the mammary gland pharmacokinetics of cefquinome after an intramammary administration and integrate pharmacokinetic/pharmacodynamic model. The pharmacokinetic profiles of cefquinome in gland tissue were measured using high performance liquid chromatograph. Therapeutic regimens covered various dosages ranging from 25 to 800 μg/gland and multiple dosing intervals of 8, 12, and 24 h. The in vivo bacterial killing activity elevated when dosage increased or when dosing intervals were shortened. The best antibacterial effect was demonstrated by a mean 1.5 log10CFU/gland visible count reduction. On the other hand, the results showed that the percentage of time duration of drug concentration exceeding the MIC during a dose interval (%T > MIC) was generally 100% because of the influence of drug distribution caused by the blood-milk barrier. Therefore, pharmacokinetic/pharmacodynamic parameter of the ratio of area under the concentration-time curve over 24 h to the MIC (AUC0-24/MIC) was used to describe the efficacy of cefquinome instead of %T > MIC. When the magnitude of AUC0-24/MIC exceeding 16571.55 h•mL/g, considerable activity of about 1.5 log10CFU/g gland bacterial count reduction was observed in vivo. Based on the Monte Carlo simulation, the clinical recommended regimen of three infusions of 75 mg per quarter every 12 h can achieve a 76.67% cure rate in clinical treatment of bovine mastitis caused by Staphylococcus aureus infection.